A meso‐Tetraaryl‐21‐carbaporphyrin: Incorporation of a Cyclopentadiene Unit into a Porphyrin Architecture. Issue 18 (1st April 2019) - Garbicz, Mateusz; Latos‐Grażyński, Lechosław
Abstract: Incorporation of a cyclopentadiene moiety into the meso ‐tetraarylporphyrin framework, using 1, 3‐bis(arylhydroxymethyl)ferrocene as a synthon, resulted in the rational synthesis of a meso ‐tetraaryl‐21‐carbaporphyrin. The molecular design preserves all essential virtues of the original tetrapyrrolic architecture of meso ‐tetraarylporphyrin, including the perfect match between the ionic radii of an inserted metal and the size of the macrocyclic (CNNN) core, and steric protection provided by thoughtfully chosen meso ‐aryl substituents. Its protonation of the inner core reveal an adjustable (trigonal versus tetrahedral) geometry. Abstract : A long‐term goal comes true : The rational incorporation of a cyclopentadiene moiety into the archetypical meso ‐aryl‐substituted porphyrin frame, using 1, 3‐bis(arylhydroxymethyl)ferrocene as a synthon, affords a prototypical meso ‐tetraaryl‐21‐carbaporphyrin. This scaffold provides a (CNNN) core that is well suited for the coordination of metals.